Analisis Efektivitas Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) pada Pemerintah Desa Selat Kecamatan Sukasada - Luh Wahyu Nirmala Devi; Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to determine the effectiveness of the management of the Village Revenue and Expenditure Budget (APBDes) in Selat Village in 2020-2023, to evaluate the management of the Village Revenue and Expenditure Budget (APBDes) in Selat Village in 2020-2023, and to determine the process of managing the Village Revenue and Expenditure Budget (APBDes) in Selat Village in 2020-2023. The method used in this study is a mixed method, namely a combination of qualitative and quantitative methods. The types of data used in this study are quantitative data in the form of the Village Revenue and Expenditure Budget Realization Report in Selat Village, Sukasada District from 2020-2023 and qualitative data in the form of interviews with informants with data collection techniques consisting of literature studies and field studies. The results of this study indicate that the Analysis of the Effectiveness of Village Revenue and Expenditure Budget Management (APBDes) in the Selat Village Government, Sukasada District for the last four years, namely 2020-2023, is in the effective category which is at a percentage of 90-100%.  Where in 2020 the budget percentage was 97.97% which can be said to be in the effective category, in 2021 the percentage reached 97.31% which was included in the effective category even though it decreased from the previous year, then in 2022 the budget percentage reached 96.92% which was also still in the effective category even though it also decreased from the previous year, and in 2023 the percentage reached 97.49% in the effective category. Evaluation of the implementation of the management of the Village Revenue and Expenditure Budget in Selat Village from 2020-2023 has been carried out properly through supervision carried out by the BPD every three months and in accordance with applicable regulations, namely achieving transparency, accountability, participation, and budget discipline. The management of the Selat Village Revenue and Expenditure Budget is carried out through several stages, namely planning, implementation, administration, reporting, and accountability, where the planning stage involves the village community which is held through village deliberations (musdes).